Understanding the importance of sport stadium visits to teams and cities through the eyes of online reviewers - Ramos, R. F.; Biscaia, R.; Moro, S.; Kunkel, T. (Leisure Studies, 2023)
This study explores the relationships among sport stadium visitors’ experiences, satisfaction, team brand image, and destination image. A text mining approach was first used to analyse 26,538 individual reviews from 17 European sport stadiums on TripAdvisor. The online reviews were then used as input to create a word frequency of each individual review and construct a structural equation model. Results indicate that the visitor experience had a strong impact on team brand image and a moderate effect on destination image. Satisfaction mediated the influence of the visitor experience on team brand image, but not on destination image. Team brand image exerted a significant but small impact on destination image. These findings show that stadium visits impact the marketing of both host teams and cities. City, leisure and stadium managers should therefore coordinate their efforts to highlight teams as part of a city’s cultural brand to generate image-based benefits for both.